Social franchising: A bibliometric and theoretical review. Issue 5 (29th July 2019) - Naatu, Felicia; Alon, Ilan
Abstract: We present a comprehensive review of social franchising literature and an integrated framework highlighting factors and theories driving the concept. Bibliometric and content analysis are used to analyze 111 articles between 2002 and 2018 from ISI Web of Science and Scopus. The following three research streams are identified: motivations for social franchising, how social franchising work, and impact of social franchising. These are integrated into a conceptual framework of five factors providing insights into value creation, performance improvement, and minimization of failures among social franchises. The review responds to calls for theoretical explorations in the field and provides bases for further studies.